1970
DOI: 10.1037/h0029184
|View full text |Cite
|
Sign up to set email alerts
|

Images and pictures in children's learning: Research results and educational implications.

Abstract: A number of experiments are reviewed that pertain to the issue of the role of imagery in children's learning. The studies reviewed include those concerned (a) with properties of learning items, (6) with properties of the elaboration of learning items, and (c) with properties of elaboration instructions. The relevant evidence is viewed developmentally, and it is concluded that the capacity for deriving optimal benefit from verbal modes of representation emerges earlier in children's learning processes than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

1971
1971
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(56 citation statements)
references
References 23 publications
2
53
1
Order By: Relevance
“…With adults and children, pictures of objects are remembered better than are the names of the objects. Illustrations often facilitate the comprehension of narrative prose by children, although the results depend upon the age, sex, and socioeconomic status of the learners, as Rohwer and his associates have found in several studies (e.g., Rohwer, 1970;Rohwer, Ammon, Suzuki, & Levin, 1971). Rohwer and Harris (1975) found that with low-SES black fourth graders, but not with high-SES white students, multimedia, especially pictures with an oral presentation, facilitated prose learning.…”
Section: Research On Cognitive Learning and Memorymentioning
confidence: 95%
“…With adults and children, pictures of objects are remembered better than are the names of the objects. Illustrations often facilitate the comprehension of narrative prose by children, although the results depend upon the age, sex, and socioeconomic status of the learners, as Rohwer and his associates have found in several studies (e.g., Rohwer, 1970;Rohwer, Ammon, Suzuki, & Levin, 1971). Rohwer and Harris (1975) found that with low-SES black fourth graders, but not with high-SES white students, multimedia, especially pictures with an oral presentation, facilitated prose learning.…”
Section: Research On Cognitive Learning and Memorymentioning
confidence: 95%
“…(Bobrow & Bower, 1969;Bower & Winzenz, 1970;Garton & Blick, 1974). However, in cases where trainees are young (Danner & Taylor, 1973;Rohwer, 1970), not sufficiently motivated (Griffith, 19791, or demonstrate difficulty in generating mnemonics without assistance (Kibler & Blick, 1972), use of instructor-generated mnemonics is recommended (see Braby,Kincaid,& Aagard,25 IN I…”
Section: Instructor-versus Trainee-generated Mnemonicsmentioning
confidence: 99%
“…A PA learning task composed of 10 actionpicture pairs was presented for the assessment of spontaneous verbalization without any naming or audio signal. These two tasks, involving static imagery and action imagery.respectively, were assumed to vary in "imagery potential" in that they offer Downloaded by [New York University] at 11:16 19 February 2015 the £ an increasing opportunity to utilize visual representation (Rohwer, 1970). Manipulation of the variable, "imagery potential" allowed an examination of whether imagery has a significant influence on spontaneous verbalization, and if so, whether differentially across the two social-class or verbal-ability groups.…”
Section: Methodsmentioning
confidence: 99%